Analisis Reaksi Stock Market Terhadap Pergantian Menteri Keuangan Tahun 2025 - Hidayatulloh Haryandanu; Ririh Pratiwi; Nila Tristiarini; Ngurah Durya (Value : Jurnal Manajemen dan Akuntansi, 2026)
The replacement of the Minister of Finance during the 2025 cabinet reshuffle was considered strategic information by the market due to its relation to investor expectations regarding fiscal policy and national economic stability. This study aims to examine differences in abnormal return (AR), cumulative abnormal return (CAR), and stock volatility in five state-owned banks listed on the Indonesia Stock Exchange before and after the event. The study employed an event study approach on the September 8, 2025 event using observation windows of 1, 3, 5, 10, and 30 days. Data were analyzed using descriptive statistics, normality tests, and paired sample t-tests or Wilcoxon signed-rank tests. The results indicate significant differences in AR and CAR in the short term, while stock volatility showed no significant difference. These findings suggest that the market responds relatively quickly to public information, consistent with the semi-strong form of the Efficient Market Hypothesis (EMH). The novelty of this study lies in the simultaneous examination of AR, CAR, and stock volatility in state-owned banks following the replacement of the Minister of Finance as a political-fiscal event.